1990
DOI: 10.1128/aac.34.10.1991
|View full text |Cite
|
Sign up to set email alerts
|

Anti-human immunodeficiency virus effects of dextran sulfate are strain dependent and synergistic or antagonistic when dextran sulfate is given in combination with dideoxynucleosides

Abstract: The effects of three molecular weight ranges of dextran sulfate on five different human immunodeficiency virus (HIV) isolates (from patients with acquired immunodeficiency syndrome), alone and in combination with dideoxynucleosides, were investigated in vitro. The higher the molecular weight range of dextran sulfate, the more potent the activity as assessed by a quantitative syncytium formation assay. Although all five HIV isolates had similar susceptibilities to the inhibitory effects of dideoxynucleosides, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…This observation was confirmed by Hayashi et al (1990) and Busso and Resnick (1990). Sohols et al (1991) showed a sub-synergistic interaction between the pyrimidine nucleoside analogues AlT, ddC, D4T and~ cyclodextrin tetradecasulfate (~-CDS), whereas the purine nucleoside analogues ddA and ddl acted mildly synergistically with~-CDS.…”
Section: In Vitro Anti-hiv Activity Of Polysulfates In Combination Wisupporting
confidence: 65%
“…This observation was confirmed by Hayashi et al (1990) and Busso and Resnick (1990). Sohols et al (1991) showed a sub-synergistic interaction between the pyrimidine nucleoside analogues AlT, ddC, D4T and~ cyclodextrin tetradecasulfate (~-CDS), whereas the purine nucleoside analogues ddA and ddl acted mildly synergistically with~-CDS.…”
Section: In Vitro Anti-hiv Activity Of Polysulfates In Combination Wisupporting
confidence: 65%
“…It has been described that the susceptibility to the antiviral effects of dextran sulphate varies among different HIV isolates and strains (Busso et al, 1990;Witvrouw et aI., 1990Witvrouw et aI., , 1991. These findings can be extended to other polyanionic compounds and most probably reflect differences in the interaction of these polyanions with the HIV envelope glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were not unexpected, since strain specific antiviral effects of dextran sulphate (Busso and Resnick, 1990;Schols et al, 1992) and rsCD4 (Daar et al, 1990) have also been reported. Passage of HIV-1 isolates through various human cell lines can alter the cellular host range tropism (Cheng-Mayer et al, 1991;Peden et al, 1991), because of differences in the cell-type-dependent glycosylation of the same viral envelope protein (Cheng-Mayer et al, 1991).…”
Section: Discussionmentioning
confidence: 53%